Islam dan Kearifan Budaya Lokal: Studi Terhadap Tradisi Penghormatan Arwah Leluhur Masyarakat Jawa - Erwin Arsadani MS (UIN Sunan Kalijaga Yogyakarta, 2012)
Islam and Java for Indonesia are like two wings of a bird. It’s like opposite each other impressed even hostile. Even been divided into two, namely students and Javanese, is unlikely to meet and continue bersebrangan. But as the two wings flapping both need each other. This is because the majority of the people of Java and Indonesia is the largest religion in the country is Islam. So the majority of people in Indonesia are Muslim Javanese. Because it would be synonymous with Muslim Javanese. Javanese people like pilgrimage, honoring the ancestors, leaders and powerful people. Java has cultural roots of respect for ancestors had to deal with Islamic monotheism. Early days of the Islamic clerics in Indonesia have discovered a way to bring together some of the culture of Java with the teachings of Islam. But there are still many Javanese culture which according to Islam is not in accordance with the principle of tawhid. It is certainly necessary theological evaluation of the scholars teaching Muslims that Islam is really rooted.